Apoptosis is triggered by melatonin in an in vivo model of ovarian carcinoma - Chuffa, Luiz Gustavo A. [UNESP]; Alves, Michelly S. [UNESP]; Martinez, Marcelo; Camargo, Isabel Cristina C. [UNESP]; Pinheiro, Patricia F.F. [UNESP]; Domeniconi, Raquel F. [UNESP]; Júnior, Luiz Antonio L. [UNESP]; Martinez, Francisco Eduardo [UNESP] (Bioscientifica, 2016)
Apoptosis plays an important role in the treatment of cancer, and targeting apoptosis-related molecules in ovarian cancer (OC) is of great therapeutic value. Melatonin (Mel) is an indoleamine displaying several anti-cancer properties and has been reported to modulate apoptosis signaling in multiple tumor subtypes. We investigated OC and the role of Mel therapy on the pro-apoptotic (p53, BAX, caspase-3, and cleaved caspase-3) and anti-apoptotic (Bcl-2 and survivin) proteins in an ethanol (EtOH)-preferring rat model. To induce OC, the left ovary was injected directly with a single dose of 100 mg 7,12-dimethylbenz(a)anthracene dissolved in 10 ml of sesame oil under the bursa. Right ovaries were used as sham-surgery controls. After developing OC, half of the animals received i.p. injections of Mel (200 mg/100 g BW per day) for 60 days. Body weight gain, EtOH consumption, and energy intake were unaffected by the treatments. Interestingly, absolute and relative OC masses showed a significant reduction after Mel therapy, regardless of EtOH consumption. To accomplish OC-related apoptosis, we first observed that p53, BAX, caspase-3, and cleaved caspase-3 were downregulated in OC tissue while Bcl-2 and survivin were overexpressed. Notably, Mel therapy and EtOH intake promoted apoptosis along with the upregulation of p53, BAX, and cleaved caspase-3. Fragmentation of DNA observed by TUNEL-positive nuclei was also enhanced following Mel treatment. In addition, Bcl-2 was downregulated by the EtOH intake and lower survivin levels were observed after Mel therapy. Taken together, these results suggest that Mel induce apoptosis in OC cells of EtOH-preferring animals.
Keywords: Anti-apoptotic protein; Melatonin; Ovarian cancer; Pro-apoptotic protein